2020
DOI: 10.3390/plants9030299
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution and Diversification of Proteins Involved in miRNA Maturation Pathway

Abstract: Small RNAs (smRNA, 19–25 nucleotides long), which are transcribed by RNA polymerase II, regulate the expression of genes involved in a multitude of processes in eukaryotes. miRNA biogenesis and the proteins involved in the biogenesis pathway differ across plant and animal lineages. The major proteins constituting the biogenesis pathway, namely, the Dicers (DCL/DCR) and Argonautes (AGOs), have been extensively studied. However, the accessory proteins (DAWDLE (DDL), SERRATE (SE), and TOUGH (TGH)) of the pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…MicroRNA (miRNA), known as non-coding small RNA with about 19 ~ 25nt in length, plays a regulatory role in various biological activities at the posttranscriptional level [7][8][9]. MiRNA, as reported, is vital in modulating airway inflammation in asthma [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA), known as non-coding small RNA with about 19 ~ 25nt in length, plays a regulatory role in various biological activities at the posttranscriptional level [7][8][9]. MiRNA, as reported, is vital in modulating airway inflammation in asthma [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses on the miRNA biogenesis machinery confirmed the presence of the majority of microprocessor proteins in representatives of all major green plant lineages, including green algae, bryophytes, ferns, and seed plants [ 41 , 161 , 162 , 163 , 164 , 165 ]. Currently living green plants ( Viridiplantae ) can be subdivided into two lineages: Chlorophyta (majority of the green algae), and Streptophyta (embryophytes and their closest algal relatives, a grade collectively known as streptophyte algae).…”
Section: Evolutionary Conservation Of Plant Microrna Biogenesis Machi...mentioning
confidence: 99%
“…Similarly to HYL1 evolutionary conservation, we found that homologs of the SE protein contain conserved SERRATE_Ars2_N—ARS2 domain architecture, regardless of the taxonomic position of the plant studied. Phylogenetic studies published in recent years have shown that single copies of SE orthologs are present in all lineages of the plant and animal kingdoms but were not identified in prokaryotes, suggesting that the SE protein encoding gene emerged as a single copy in the last eucaryotic common ancestor (LECA) [ 161 , 163 , 164 ]. Interestingly, in representatives of some embryophytes, such as moss Physcomitrium patens, water lily Nymphaea colorata or parasitic dicot Striga asiatica, the SE gene underwent a duplication event.…”
Section: Evolutionary Conservation Of Plant Microrna Biogenesis Machi...mentioning
confidence: 99%
“…Furthermore, JsCBF5 and JsICE1b had more protein interaction relationships compared to other CBF and ICE proteins. In plants, miRNAs play many biological functions by regulating the expression of target genes, such as in clod tolerance [44][45][46]. There is no published miRNA database in psRNATarget for walnut species, so we predicted the interaction network between the CBF and ICE proteins in walnuts and the putative miRNA in Arabidopsis for target prediction.…”
Section: Protein-protein and Protein-microrna Interaction Predictionsmentioning
confidence: 99%